The evening spider - Arsenault, Emily (William Morrow, an imprint of HarperCollinsPublishers, 2016)
In 1855 New England, young mother Frances Barnett's obsession with the details of a local murder trial lead her to a mental institution, while in the present day, young mother Abby Bernacki discovers Barnett's diary and finds unsettling parallels with her own life.